On the Design and Performance Analysis of Flexible Planar Monopole Ultra-Wideband Antennas for Wearable Wireless Applications - Deepa Thangarasu; Rama Rao Thipparaju; Sandeep Kumar Palaniswamy; Malathi Kanagasabai; Mohammed Gulam Nabi Alsath; Devisowjanya Potti; Sachin Kumar (International Journal of Antennas and Propagation)
With the promising developments in wearable communication technology, attention towards flexible electronics is increasing day-by-day. This study presents flexible low-profile ultra-wideband (UWB) antennas for wearable applications. The antenna comprised of a modified dewdrop-inspired radiator and a defected ground plane and has an impedance bandwidth of 3.1–10.6 GHz. The antenna flexibility is investigated using four different substrates (polyester, polyamide, denim, and Teslin) and tested on a cotton shirt and a high-end Res-Q jacket to evaluate their performance stability for body-worn applications. The fabricated planar dewdrop-shaped radiator (PDSR) antennas have a radiation efficiency of >90%, a gain of >4 dBi, and a group delay variation of fewer than 0.5 ns. The antenna conformability is measured by placing the fabricated antennas on various curved and nonplanar parts of the human body. The aforementioned antennas offer better flexibility for different bent conditions. The specific absorption rate (SAR) of the designed antennas is investigated to determine their wearability, and values are found to be less than 0.2 W/Kg. Also, the received signal strength (RSS) is discussed in order to analyze signal attenuation, and the performance analysis of the antennas is compared.